Pecan cultivation: general aspects - Fronza,Diniz (2018)
ABSTRACT: Given the increasing investment in the pecan production in southern Brazil, it becomes necessary researches, assisting in solve problems and proposition of technical and methodology to enhance this production chain. Thus, the present review aimed to survey the existing information about the culture, both on the world and the Brazilian scene. Issues related to botany, climate and soil requirements, alignment and planting density, cultivars, pests and diseases, among other technical aspects of this culture will be addressed. Pecan nut presents nutraceutical properties that are beneficial to human health, which has increased its demand from consumers. However, there are few research results with pecan nut in Brazil and there are many gaps in scientific knowledge about this culture, especially as regards the management of pests and diseases control, irrigation and nutrition, in Brazilian conditions.